Análise comparativa de métodos de medição de parâmetros acústicosem salas de pequeno porte - Calebe Giaculi Junior (2017)
This work presents the results of acoustic parameter analysis for tests performed in two classrooms of equal dimensions at the School of Music of the Universidade Federal de Minas Gerais (rooms 06 and 08). Only one of them has changeable acoustic paneling, which generated 3 types of acoustic conditions: Room 06 with open panels (little reverberation), Room 06 with closed panels and Room 08 (highly reverberated). Acoustic parameters were calculated at intervals of one third of octave using three measurement methods: exponential sine sweep, impulsive source and interrupted noise source. Either an omnidirectional source (dodecahedron) or an audio monitor was used. The source was placed at three positions and the microphone at five measuring positions to analyze the variation caused by changes in positions. From the measurements, it was possible to compare the influence on the calculation of the reverberation time caused by the type of sound source, by the method of measurement, and by the positions of source andmicrophone. For the frequency range between 100 Hz and 10 kHz, the measurement methods did not present significant discrepancies, which is an evidence that all of them are reliable. However for the subwoofer frequencies, i.e. from 25 Hz to 80 Hz, the methods exhibited large inconsistencies, and often the reverberation time could not be calculatedfrom T20. In this frequency range only the noise interrupted method presented values within the expected range for all rooms. A preliminary analysis was also carried out to calculate early decay time (EDT), clarity (C80), definition (D50) and central time (TS). These descriptors were used to compare the differences between using an audio monitor e a dodecahedron as sound source. Only EDT did not show any difference with respect to sound source directivity. Finally, it was verified that the variation of the acoustic field with the relative position between source and microphone for T20 is inversely proportional to the reverberation of the room, measured by the relative standard deviation (RSD).